Internasionalisasi Bahasa Negara Melalui Pelatihan Pengajar BIPA di Perancis - Sunendar, Dadang; Hardini, Tri Indri; Sunendar, Neidya Fahma (Empowerment: Jurnal Pengabdian pada Masyarakat, 2026)
As the national language, Indonesian plays a strategic role as a national identity and an instrument of global diplomacy. In line with Law Number 24 of 2009, the internationalization of Indonesian is carried out through the Indonesian Language for Foreign Speakers (BIPA) program. This research aims to analyze the position of Indonesian, language politics and planning, and BIPA development strategies through a Participatory Action Research (PAR) approach. The PAR method was implemented through planning, action, and reflection with BIPA teachers in France during a training session held on July 17–18, 2025, at the Indonesian Embassy in France. The results indicate that Indonesian has strengths in terms of regulations, history, and number of speakers, as well as significant potential to become an international language. However, weaknesses remain, such as low public ideological understanding and limited vocabulary. The implementation of language policy also faces challenges in the public sphere. The BIPA development strategy emphasizes ongoing training, strengthening teaching materials, research, and cross-institutional collaboration. The PAR approach has proven effective in producing contextual and sustainable solutions.